2019
DOI: 10.1136/bmj.l1516
|View full text |Cite
|
Sign up to set email alerts
|

Pre-eclampsia and risk of later kidney disease: nationwide cohort study

Abstract: ObjectiveTo investigate associations between pre-eclampsia and later risk of kidney disease.DesignNationwide register based cohort study.SettingDenmark.PopulationAll women with at least one pregnancy lasting at least 20 weeks between 1978 and 2015.Main outcome measureHazard ratios comparing rates of kidney disease between women with and without a history of pre-eclampsia, stratified by gestational age at delivery and estimated using Cox regression.ResultsThe cohort consisted of 1 072 330 women followed for 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
96
3
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 31 publications
3
96
3
5
Order By: Relevance
“…However, most studies in this systematic review reported strong associations even after controlling for, or excluding, women with prepregnancy hypertension 8,9,[27][28][29][30][31][35][36][37][38][39] or obesity. 28,32,33,35,39,42 Preeclampsia has been proposed as a cause of lasting vascular endothelial dysfunction, possibly associated with elevated levels of soluble fms-like tyrosine kinase-1, an antiangiogenic protein…”
Section: Discussionmentioning
confidence: 69%
“…However, most studies in this systematic review reported strong associations even after controlling for, or excluding, women with prepregnancy hypertension 8,9,[27][28][29][30][31][35][36][37][38][39] or obesity. 28,32,33,35,39,42 Preeclampsia has been proposed as a cause of lasting vascular endothelial dysfunction, possibly associated with elevated levels of soluble fms-like tyrosine kinase-1, an antiangiogenic protein…”
Section: Discussionmentioning
confidence: 69%
“…Although spontaneous preterm delivery was independently associated with CKD and ESKD in our study, the results suggest that preeclampsia, and to a lesser extent SGA, has a greater impact on renal risk than preterm delivery. Preeclampsia has been reported to increase the risk of maternal CKD [22][23][24][25] and ESKD [11,13,15,22] previously.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively little is known about its long-term effects on the kidney function later in life, and data available reveal conflicting results. While some studies report kidney dysfunction can be resolved in most women with a history of PE [10][11][12][13], it has been shown that some women with PE may experience decreased GFR and/or persistent proteinuria and/or increased risk of CKD after PE [9,[14][15][16][17][18], discrepancies which may be partly explained by differences in ethnicities, study design, definition of kidney function, and limited follow-up durations after pregnancy.…”
Section: Introductionmentioning
confidence: 99%